Adam Ferguson and the Complex Relationship between Commerce and Virtue (Polis (Santiago), 2018)
During the Enlightenment period, a divulged discourse proclaimed the supremacy of the economic sphere above the political and ethical ones. However, Adam Ferguson, one of the main exponents of the Scottish Enlightenment, did not accept thus. To him, the arrival of commercial society —the market—,decisive for economic progress, also brought about a disequilibrium which threatened the future of society. The political element was fundamental in order to preserve societies. Twom models were thus confronted: one based on the principle that seemed able to guide human relationships universally: economic exchange; an on the other hand, an image of civil society based on the virtuosity of the citizen. Ferguson was a defender of the second model; for him, a virtuous man is not the one who serenely contemplates what is happening around him, but one who through his active exercise of virtuosity looks up to the political sphere. In this way, virtuosity and politics become closely connected.
Keywords: Adam Ferguson; civic virtue; commerce; corruption